Electronic transport through short dsDNA measured with mechanically controlled break junctions: New thiol–gold binding protocol improves conductance. Issue 11 (30th August 2013) - Liu, S. P.; Artois, J.; Schmid, D.; Wieser, M.; Bornemann, B.; Weisbrod, S.; Marx, A.; Scheer, E.; Erbe, A.; Frauenheim, Thomas; Niehaus, Thomas; Repp, Jascha; et al.
<x xml:space="preserve">Abstract</x> It is shown that double‐stranded DNA which is directly coupled to gold via a modified thymidine base exhibits a higher conductance than reported for DNA coupled to metal electrodes using different binding schemes. The measurements of electrical conductance are performed in a mechanically controlled break junction setup in aqueous solution and in high vacuum at room temperature. The current–voltage characteristics obtained in vacuum can be understood if a single molecular energy level determines the transport.